Studying the effect of fluid viscosity difference on the performance of centrifugal and external gear pumps using an experimental circuit that simulates blood circulation in the human body. - رحال, علاء; أيوب حسن; فاتن عجيب (Latakia University Journal -Engineering Sciences Series, 2023)
In the research, a mechanical model was designed and tested to explain mechanism of the circulatory system by replacing each component of the circulatory system with an engineering part that performs its work. Then the device was run using two fluids of different viscosities: the first is distilled water and the second is a fluid with a viscosity similar to the viscosity of blood, and compare the basic parameters of the pumps’ work such as pressure, flow rate and energy consumption to obtain similar values for systolic and diastolic blood pressure. the experiments has shown that: The pump that represents the left ventricle pump, which is a centrifugal pump, gave a systolic pressure P=118.72 mm Hg at a flow rate Q=78.3 L/hour with a power consumption of 29.15 W When the device was tested by using distilled water, by using a solution (glycerin-water) with a viscosity µ=0.003517 N.S/m2, the pump gave a systolic pressure P=116 mm Hg at a volumetric flow rate of Q=63 L/hour with an energy consumption of 39.28W. While the pump representing the right ventricle pump, which is an external gears pump, gave a systolic pressure of P=102.74 mm Hg at a flow rate Q=15 L/hour with an energy consumption of 10.62W by using distilled water, and using a solution (glycerin- water), the pump gave a systolic pressure of P=119.63 at a volumetric flow rate of Q=12.5 L/hour with a power consumption of 19.72 W.